PENINGKATAN KEMAMPUAN FISIK MOTORIK KASAR ANAK KELOMPOK B MELALUI PERMAINAN FOOTPRINTS DI TK ABA 7 MALANG - Yesi Anggraini (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
The background of this research is the undeveloped physical abilities of gross motor skills of group B children in TK ABA 7 Malang. The purpose of this study was to improve the physical abilities of gross motor skills of group B children in TK ABA 7 Malang through footprints games. The design of this study uses classroom action research (CAR), this research model uses a model developed by Kemmis & MC. Taggart. This research was conducted in TK ABA 7 Malang, the research subjects were children of B2 group TK ABA 7 Malang, with a total of 21 children, consisting of 10 boys and 11 girls.